2018
DOI: 10.1186/s12884-018-1819-9
|View full text |Cite
|
Sign up to set email alerts
|

Report on an international workshop on kangaroo mother care: lessons learned and a vision for the future

Abstract: BackgroundGlobally, complications of prematurity are the leading cause of death in children under five. Preterm infants who survive their first month of life are at greater risk for various diseases and impairments in infancy, childhood and later life, representing a heavy social and economic burden for families, communities and health and social systems. Kangaroo mother care (KMC) is recommended as a beneficial and effective intervention for improving short- and long-term preterm birth outcomes in low- and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 37 publications
2
30
0
4
Order By: Relevance
“…KMC was initially proposed as an alternative to the conventional contemporary method of care for lowbirthweight infants and was introduced to some lowincome countries including Bangladesh, Malawi, Nepal, etc. in the 1980s and 1990s [3]. In these countries, the prevalence of prematurity/low birth weight is high while medical resources are limited, KMC was performed as an alternative to incubators or warmers [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KMC was initially proposed as an alternative to the conventional contemporary method of care for lowbirthweight infants and was introduced to some lowincome countries including Bangladesh, Malawi, Nepal, etc. in the 1980s and 1990s [3]. In these countries, the prevalence of prematurity/low birth weight is high while medical resources are limited, KMC was performed as an alternative to incubators or warmers [4].…”
Section: Introductionmentioning
confidence: 99%
“…The main facilitators to the practice of KMC included "support from hospital management", "mother-infant attachment" and "support from family, friends and other mentors" [21][22][23][24]. Despite there are studies published on barriers and facilitators of implementing KMC in many Asian countries including Nepal, India, Pakistan, Bangladesh, Vietnam, Philippines and Indonesia [3,22,25,26], we believe that China may have some unique barriers and facilitators to the practice of KMC due to its specific policies, resources and traditional culture and we are not aware of any prior published studies in China examining these barriers and facilitators.…”
Section: Introductionmentioning
confidence: 99%
“…Despite there are studies published on barriers and facilitators of implementing KMC in many Asian countries including Nepal, India, Pakistan, Bangladesh, Vietnam, and Indonesia [3,22,25], we believe that China may have some unique barriers and facilitators to the practice of KMC due to its speci c policies, resources and traditional culture and we are not aware of any prior published studies in China examining these barriers and facilitators.…”
Section: Introductionmentioning
confidence: 89%
“…Studies from other countries have found that at hospital and health system level, the absence of leadership, in exible visitation policies for parents, insu cient sta ng levels, and insu cient training were barriers to KMC [3]. Evidence from other Asian countries shows that leadership and governance, the presence of essential medical products, the health workforce and health nancing were important factors in uencing the adoption of KMC [22,25,36].…”
Section: Barriers and Facilitators At Hospital Levelmentioning
confidence: 99%
See 1 more Smart Citation